2014
DOI: 10.5194/tc-8-991-2014
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication: Light-absorbing impurities can reduce the density of melting snow

Abstract: Abstract. Climatic effects of black carbon (BC) deposition on snow have been proposed to result from reduced snow albedo and increased melt due to light-absorbing particles. In this study, we hypothesize that BC may decrease the liquidwater retention capacity of melting snow, and present our first data, where both the snow density and elemental carbon content were measured. In our experiments, artificially added light-absorbing impurities decreased the density of seasonally melting natural snow. No relationshi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 10 publications
4
39
0
Order By: Relevance
“…Although the change in grain size is on the order of the uncertainty in grain size retrieval, it is not the absolute values that are important but rather the trend. A decrease in surface grain size in the presence of high impurity content was also observed in the daily field observations in 2013 by Skiles (2014), when the dust layers coalesced at the surface and skies were clear both grain sizes and density in the surface layers decreased and surface roughness increased, consistent with observations in other regions (Meinander et al, 2014). Skiles (2014) and Painter et al (2013) as well as the results in this paper suggest that the intensification of snowmelt by dust in the visible wavelengths results in destructive metamorphism near the snow-atmosphere interface and snowmelt infiltration with refreezing and snow grain coarsening at depths of approximately 2 to 10 cm.…”
Section: Uncertainty and Error Analysissupporting
confidence: 76%
See 1 more Smart Citation
“…Although the change in grain size is on the order of the uncertainty in grain size retrieval, it is not the absolute values that are important but rather the trend. A decrease in surface grain size in the presence of high impurity content was also observed in the daily field observations in 2013 by Skiles (2014), when the dust layers coalesced at the surface and skies were clear both grain sizes and density in the surface layers decreased and surface roughness increased, consistent with observations in other regions (Meinander et al, 2014). Skiles (2014) and Painter et al (2013) as well as the results in this paper suggest that the intensification of snowmelt by dust in the visible wavelengths results in destructive metamorphism near the snow-atmosphere interface and snowmelt infiltration with refreezing and snow grain coarsening at depths of approximately 2 to 10 cm.…”
Section: Uncertainty and Error Analysissupporting
confidence: 76%
“…Besides snowmelt, snowfall impacts snowpack properties very rapidly and, thus, it is important to capture temporal changes in addition to spatial patterns. For example, Molotch et al (2004) showed that spatially distributed snowmelt models benefit significantly from incorporating snow albedo estimates derived from the NASA/JPL Airborne Visible/Infrared Imaging Spectrometer (AVIRIS) data instead of using empirical basin-wide snow albedo assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…However, different melting conditions, or different hydrophobic properties of the contaminants, may reverse the process, accumulating the dirt on the surface (Conway et al, 1996;Meinander et al, 2014). Such snow was not measured…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were conducted in different regions in Finland, in 2011 and, with the general aim to monitor and quantify the effects of soot on the albedo and physical properties of the snowpack. To this end, absorbing aerosols of different origins were deposited on a natural snowpack in a controlled way and the changes in the snowpack properties were measured (Meinander et al, 2014;Svensson et al, 2015). In this Figure 1.…”
Section: J I Peltoniemi Et Al: Reflectance Of Contaminated Snowmentioning
confidence: 99%
See 1 more Smart Citation